It's Easy to Be One of the Intelligentsia. (1st October 2016) - Zanerv, Dmitrii
Abstract : Dmitrii Zanerv points out the unusual and continuing popularity of Arkady and Boris Strugatsky, who are still read all over the world. After outlining their biographies, Zanerv identifies their three great works and discusses the reason for the decline in quality or importance of their later writings. He concludes that they are not as great as they seemed to Soviet readers who had not read widely in science fiction from other cultures, though to this date they are still the best diagnosticians of the Soviet condition.